(3GdeNJGQ ef eNJUQ cJGH GdQhMs - (3eLghds; (3GHf bje GdLhRjI , eMeO Hf CHj HcQ Hf GjhH Hf SYO GdRQYj GdOeTbj, TeS GdOjf CHh YHO Gddg,J (B751 (3g` s
(3ChdgG (B:s
(3hHYO agPG GdJYdjb ENJUQJ ajg ebGUO cJGH GdQhM eG ENJUQg GdYdGeI TeS GdOjf eMeO Hf Gdbje GdMfHdj s
(3BNQgG (B:s
(3hGYO dcd efgG eG jfGSHI hdaX GdMRe s
(3GdfSNI HgG MhGTs
(3eNJUQ GdQhM dGHf bje GdLhRjI GfXQ cTa GdXfhf L (B2 (3U`(B1421s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
Keywords: (3GdJhMjO hGdedd hGdfMds